Blood filtering system for COVID-19 management: novel modality of the cytokine storm therapeutics - Chavda, Vivek P.; Raval, Nidhi; Sheta, Soham; Vora, Lalitkumar K.; Elrashdy, Fatma; Redwan, Elrashdy M.; Uversky, Vladimir N.; Ertas, Yavuz Nuri (Frontiers in Immunology, 2023)
The newly emerged coronavirus (SARS-CoV-2) is virulent, contagious, and rapidly gained many mutations, which makes it highly infectious and swiftly transmissible around the world. SARS-CoV-2 infects people of all ages and targets all body organs and their cellular compartments, starting from the respiratory system, where it shows many deleterious effects, to other tissues and organs. Systemic infection can lead to severe cases that require intensive intervention. Multiple approaches were elaborated, approved, and successfully used in the intervention of the SARS-CoV-2 infection. These approaches range from the utilization of single and/or mixed medications to specialized supportive devices. Both extracorporeal membrane oxygenation (ECMO) and hemadsorption are used in combination or separately for severely ill COVID-19 patients with acute respiratory distress syndrome to support and release the etiological agents responsible for the “cytokine storm” behind this syndrome. The current report discusses hemadsorption devices that can be used as part of the supportive treatment for the COVID-19-associated cytokine storm.